Postbiotics and their biotherapeutic potential for chronic disease and their feature perspective: a review - Asefa, Zerihun; Belay, Abera; Welelaw, Eyuel; Haile, Meseret (Frontiers in Microbiomes, 2025)
Postbiotics, which are bioactive compounds derived from the metabolic processes of probiotics, are gaining recognition as a promising alternative for managing chronic diseases without the need for live microorganisms, positioning them as a valuable strategy in biotherapeutics that offers both curative and preventive techniques in modern medicine. This paper provides a comprehensive review of the potential health benefits of postbiotics, particularly concerning noncommunicable diseases like diabetes, cancer, obesity and cardiovascular conditions, which present significant global health challenges. We explore the various mechanisms by which postbiotics exert their beneficial effects, including immune modulation to enhance the body’s immune response and reduce inflammation, as well as improving gut barrier function to maintain gut integrity and prevent increased intestinal permeability. Additionally, the antioxidant properties of postbiotics play a critical role in neutralizing oxidative stress, which is linked to the progression of chronic diseases. Despite the encouraging insights into their health benefits, we highlight the urgent need for further research to clarify the specific roles of different postbiotic components. A deeper understanding of these mechanisms is essential for developing targeted preventive healthcare applications, and by advancing this knowledge, we aim to create innovative strategies that could significantly enhance health outcomes for at-risk populations. Ultimately, integrating postbiotics into health interventions has the potential to improve preventive care and contribute to the overall well-being of affected individuals and communities.